PENGEMBANGAN BAHAN AJAR GAMIFIKASI MATEMATIKA SISWA MTs - Rizki Wahyu Yunian Putra; Aan Subhan Pamungkas (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2019)
This research aims to gain quality learning materials gamifikasi of mathematics seen in terms of feasibility, attractiveness, as well as to obtain responses to learners and educators in learning materials that have been developed. The subject developed was set. One of the basic necessities in the process of teaching and learning are the presence of materials of interest. The research method used i.e. research and development (Research and Development) consisting of: (1) model development, (2) development of procedures, and (3) product trials that are components in research development (developmental Research). Based on the analysis of data obtained from some experts that is media experts, linguists, and the material can be stated that the learning materials gamifikasi of mathematics worthy of use, and the results of the analysis of data obtained from educators and learners is expressed that the materials developed are very interesting. So that shows that learning materials gamifikasi mathematics developed can be used as a learning resource for learners and educators Mts/junior high school class VII.Keywords: Gamifikasi Learning Materials for Mathematics